2021
DOI: 10.1097/pts.0000000000000827
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organizational Climate and Clinician Morale on Seclusion and Physical Restraint Use in Inpatient Psychiatric Units

Abstract: Reducing seclusion and restraint use is a prominent focus of efforts to improve patient safety in inpatient psychiatry. This study examined the poorly understood relationship between seclusion and restraint rates and organizational climate and clinician morale in inpatient psychiatric units.Methods: Facility-level data on hours of seclusion and physical restraint use in 111 U.S. Department of Veterans Affairs (VA) hospitals in 2014 to 2016 were obtained from the Centers for Medicare & Medicaid Services. Respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…While nurses in our study found ways to learn from or cope with their emotions following stressful S/R events, it is also worth noting the link between nurses' level of stress and the use of S/R. In a recent study by Anderson et al (2021), the authors found that inpatient psychiatric settings with greater staff burnout had a higher incidence of physical restraint use. They proposed that clinicians with higher burnout have a lower threshold for restricting a patient's freedom of movement in response to violent or disruptive behaviour (Anderson et al, 2021).…”
Section: Emotional Experiencementioning
confidence: 64%
See 1 more Smart Citation
“…While nurses in our study found ways to learn from or cope with their emotions following stressful S/R events, it is also worth noting the link between nurses' level of stress and the use of S/R. In a recent study by Anderson et al (2021), the authors found that inpatient psychiatric settings with greater staff burnout had a higher incidence of physical restraint use. They proposed that clinicians with higher burnout have a lower threshold for restricting a patient's freedom of movement in response to violent or disruptive behaviour (Anderson et al, 2021).…”
Section: Emotional Experiencementioning
confidence: 64%
“…In a recent study by Anderson et al (2021), the authors found that inpatient psychiatric settings with greater staff burnout had a higher incidence of physical restraint use. They proposed that clinicians with higher burnout have a lower threshold for restricting a patient's freedom of movement in response to violent or disruptive behaviour (Anderson et al, 2021). Indeed, burnout among mental healthcare providers has been tied to less empathic and more dehumanizing attitudes towards patients who are deemed as 'difficult' or 'challenging' (Bowers et al, 2010;Pereira-Lima & Loureiro, 2015).…”
Section: Emotional Experiencementioning
confidence: 98%
“… 25 , 26 The regional variation may be because of more closely connected hospital organizational cultures, similar staffing patterns, regional laws, and inconsistent adoption of evidence-based practices at large health systems in the western United States. 27 , 28 Future studies should investigate how regional characteristics, such as access to mental health services and local practices, impact the use of restraints.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing the abovementioned conflicts resulted in the final inclusion of nine articles for review. [32][33][34][35][36][37][38][39][40]…”
Section: Eligibility Criteria and Study Selectionmentioning
confidence: 99%
“…Of the nine studies, only five studies indicated a significant association between psychological safety and patient safety. 35,36,37,39,40 However, all five studies need further qualification to fully appreciate the complexity in linking psychological safety and patient safety. Anderson et al, 36 in a sample of US Veteran Affairs inpatient psychiatry clinicians, found that units with lower psychological safety reported a greater use of restraints with patients, but also found that units with higher psychological safety utilized seclusion more.…”
Section: Is There a Relationship Between Psychological Safety And Pat...mentioning
confidence: 99%